Do psychopathic traits predict criminal activity? - M. Antonella Mancino; Tarek Attia (Journal of Applied Economics, 2022)
Psychopathy evidence is frequently used for court decisions involving young criminals, claiming that is it an important predictor of crime. We investigate the effect of psychopathy on crime using a unique panel dataset of young offenders, which allows to analyze several dimensions of psychopathy, controlling for a wide range of usually unobservable characteristics. We find that psychopathy is an important predictor of crime. We show that the effect is two times larger (and closer to usual estimates) when measures of cognitive and non-cognitive skills are not accounted for, highlighting the importance of having comprehensive data on individual heterogeneity to isolate the effect of psychopathy on crime from the effect of confounding factors. Our results are robust to alternative measures of psychopathy and criminal participation. The findings suggest that court decisions should focus both on psychopathic characteristics and skills when deciding about an adolescenc's sentence.
Keywords: 330; psychopathy; recidivism; skills; Youth